2023
DOI: 10.1038/s41598-023-43206-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of tuberculosis lymphadenitis, risk factors, and rifampicin resistance at Adama city, Ethiopia: a cross-sectional study

Hawi Kumbi,
Dawit Yihdego Reda,
Manyahlehal Solomon
et al.

Abstract: Mycobacterium tuberculosis complex has an impact on public health and is responsible for over one million deaths per year. Substantial numbers of people infected with M. tuberculosis can develop tuberculosis lymphadenitis; however, there is a limited study in Adama, Ethiopia. The aim of this study was to determine the magnitude of Tuberculosis lymphadenitis, its predictors, and rifampicin-resistance gene-positive M. tuberculosis. A total of 291 patients with enlarged lymph nodes were recruited from May 2022 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Rifampicin mono-resistance tuberculosis of the lymph nodes is relatively infrequently reported and few studies have reported the prevalence ranging from 2.9-6.5% [ 11 ]. Diagnosis of primary rifampicin mono-resistant tuberculosis is mainly based on fine-needle aspiration cytology and identification of the Mycobacterium tuberculosis with resistance to rifampicin on the cartridge-based nucleic acid amplification test and culture [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rifampicin mono-resistance tuberculosis of the lymph nodes is relatively infrequently reported and few studies have reported the prevalence ranging from 2.9-6.5% [ 11 ]. Diagnosis of primary rifampicin mono-resistant tuberculosis is mainly based on fine-needle aspiration cytology and identification of the Mycobacterium tuberculosis with resistance to rifampicin on the cartridge-based nucleic acid amplification test and culture [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…AHMC serves as a referral hospital for the people residing in the East Shewa Zone of the Oromia Regional State and adjacent regions. Sociodemographic and clinical data was collected using a structured preprepared format [ 16 ]. For the diagnosis of TBL, the ZN staining technique, FNAC, and GeneXpert were used.…”
Section: Methodsmentioning
confidence: 99%
“…The air-dried FNA smears were stained with Wright’s stain according to the SOPs [ 16 ] and examined microscopically by experienced pathologists. The FNAC shows up the epithelioid granulomas, and the epithelioid granulomas with multinucleated giant cells, caseous necrosis, degenerating inflammatory cells and liquefied necrotic materials were considered cytologically positive for tuberculosis [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations